Analysis of Competition Fronting the Popularity of Content in Social Networks - Siham Hafidi; Mohamed Baslam; Rachid El Ayachi (International Journal of Informatics and Communication Technology (IJ-ICT), 2017)
In recent years, on the Internet, there is a real phenomenon: the development of social networks that are becoming more popular and more used. Social networks have millions of users worldwide. This provides an opportunity for companies to reach out a large and diverse audience for their advertising campaigns. They do this by creating and spreading content across the social network, which will increase the chance of visibility for their contents, which for them is the assurance of being popular. Every content requires time to reach a specific destination on the networks. In this article, we study competition between several contents that look for attracting more consultations, each characterized by some given popularity. There is competition between the contents of a limited set of destinations. We first model our system, we then study the competition between contents by using the game theory to analyze this behavior. We finally provide numerical results, which provide insights into the effect of various parameters of the system.